Infrastructural Facilities, Learning, and Human Resources in the Pre-Service Secondary-Level Teacher Education Programme in Rajasthan - Rathor, Kapil; Panigrahi, Manas Ranjan (Innovare Journal of Education, 2025)
The quality of pre-service secondary teacher education is critically dependent on the adequacy of infrastructural facilities, human resources, and learning resources available in training institutions. This study was undertaken to (i) analyze the infrastructure facilities in pre-service secondary teacher education programs in Rajasthan in relation to the National Council of Teacher Education (NCTE) Regulation 2014, and (ii) examine the availability of human and learning resources within these programs against the same regulatory framework. Adopting a mixed-method approach, data were collected from a sample of 60 teacher educators and 250 student teachers drawn from 11 teacher education institutions affiliated with four universities in Rajasthan. Structured questionnaires designed for teacher educators and student teachers formed the primary tools of data collection. The findings reveal several critical gaps. A significant shortage of qualified teaching and non-teaching staff was observed, leading to high pupil–teacher ratios and inadequate academic support. Nearly one-third of faculty members were perceived as lacking in subject mastery, language proficiency, and pedagogical clarity, with a notable absence of method teachers for languages, vocational subjects, arts, and physical education. Learning resources were found to be insufficient, with libraries poorly stocked with updated reference materials and journals, while information and communication technology (ICT), education technology (ET), and language labs were either non-functional or missing. Infrastructural facilities such as smart classrooms, hostels, playgrounds, and common rooms were either inadequate or below prescribed standards. Furthermore, institutional linkages with state-level educational bodies like Cluster Resource Center, Block Resource Centers, and Rashtriya Madhyamik Shiksha Abhiyan were minimal, restricting practice-oriented exposure for student teachers. The study concludes that pre-service secondary teacher education institutions in Rajasthan fall short of the NCTE (2014) requirements in infrastructure, human, and learning resources. Strengthening these dimensions is imperative for ensuring quality teacher preparation aligned with contemporary policy expectations.